2008
DOI: 10.1534/genetics.107.084558
|View full text |Cite
|
Sign up to set email alerts
|

Wispy, the Drosophila Homolog of GLD-2, Is Required During Oogenesis and Egg Activation

Abstract: Egg activation is the process that modifies mature, arrested oocytes so that embryo development can proceed. One key aspect of egg activation is the cytoplasmic polyadenylation of certain maternal mRNAs to permit or enhance their translation. wispy (wisp) maternal-effect mutations in Drosophila block development during the egg-to-embryo transition. We show here that the wisp gene encodes a member of the GLD-2 family of cytoplasmic poly(A) polymerases (PAPs). The WISP protein is required for poly(A) tail elonga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
134
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(142 citation statements)
references
References 62 publications
(96 reference statements)
8
134
0
Order By: Relevance
“…GLD-2 was identified as a regulatory cytoplasmic poly(A) polymerase that controls germline progression through meiosis in C. elegans and Schizosaccharomyces pombe (Read et al 2002;Saitoh et al 2002;Wang et al 2002). Recently, it was reported that in Drosophila a GLD-2 homolog is required for long-term memory (Kwak et al 2008) and oogenesis (Cui et al 2008). Mammalian GLD-2 is expressed in many tissues and localizes in both the nucleus and cytoplasm (Nakanishi et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…GLD-2 was identified as a regulatory cytoplasmic poly(A) polymerase that controls germline progression through meiosis in C. elegans and Schizosaccharomyces pombe (Read et al 2002;Saitoh et al 2002;Wang et al 2002). Recently, it was reported that in Drosophila a GLD-2 homolog is required for long-term memory (Kwak et al 2008) and oogenesis (Cui et al 2008). Mammalian GLD-2 is expressed in many tissues and localizes in both the nucleus and cytoplasm (Nakanishi et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The poly(A) tail of cyclin A mRNA is short during prophase I arrest, and its lengthening correlates with appearance of the protein at oocyte maturation. It remains to be determined how this polyadenylation is controlled, but a likely possibility is that it may involve the GLD2 poly(A) polymerase shown to polyadenylate other mRNAs at maturation (2,33). The poly(A) tail is further increased at egg activation in a mechanism that requires active PNG kinase, and this may contribute to efficient translation of Cyclin A during early embryogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Translation of Cyclin B also is promoted by Drosophila CPEB, called ORB ( figure 2c). In addition, a GLD-2 homologue is required at maturation for polyadenylation and translation of many proteins, including the Drosophila orthologue of Mos and a meiosis-specific activator of the APC/C called Cortex [42,101,102].…”
Section: Developmental Control Of the Cell Cycle Via Translational Rementioning
confidence: 99%